How would you diagram this conditional statement?

ioannisk
Posts: 83
Joined: Wed Jul 31, 2013 11:38 am

How would you diagram this conditional statement?

Postby ioannisk » Wed Oct 23, 2013 12:01 pm

"Only wrong actions would be expected to reduce the aggegate well-being of a person"

From this statement, the conditional diagram would be reduce the aggegate well-being of a person ----> Wrong actions

correct?

User avatar
JWP1022
Posts: 269
Joined: Mon Dec 03, 2012 10:15 pm

Re: How would you diagram this conditional statement?

Postby JWP1022 » Wed Oct 23, 2013 12:16 pm

Basically. More exactly:

Something Reduces Aggregate Well Being --> Expected to be Wrong Actions

I would be wary, though. This seems like a sentence with conditional phrasing that might really need to be diagrammed to answer the question. What PT/S/Q is this?

ioannisk
Posts: 83
Joined: Wed Jul 31, 2013 11:38 am

Re: How would you diagram this conditional statement?

Postby ioannisk » Wed Oct 23, 2013 12:19 pm

JWP1022 wrote:Basically. More exactly:

Something Reduces Aggregate Well Being --> Expected to be Wrong Actions

I would be wary, though. This seems like a sentence with conditional phrasing that might really need to be diagrammed to answer the question. What PT/S/Q is this?

It was the free pretpest june 2007 section 2 LR, one of the questions in the 20s.

but that wasn't a direct statement, it was actually casual not conditionional in the passage. I just was thinking how to diagram it if it was conditional.

User avatar
A → B ⊨ ¬B → ¬A
Posts: 628
Joined: Tue Oct 23, 2012 5:32 pm

Re: How would you diagram this conditional statement?

Postby A → B ⊨ ¬B → ¬A » Wed Oct 23, 2013 4:32 pm

ioannisk wrote:"Only wrong actions would be expected to reduce the aggegate well-being of a person"

From this statement, the conditional diagram would be reduce the aggegate well-being of a person ----> Wrong actions

correct?


Ew • (∀x){[Ax • (x ≠ w)] → ~Ex}

wrong is expected to reduce the aggregate well-being of a person, and for all x, if x is an action and x is different from wrong, then x is not expected to reduce the aggregate well-being of a person

E for expected to reduce the aggregate well-being of a person
w for wrong
A for action

User avatar
Jeffort
Posts: 1897
Joined: Wed Jun 18, 2008 4:43 pm

Re: How would you diagram this conditional statement?

Postby Jeffort » Wed Oct 23, 2013 5:07 pm

A → B ⊨ ¬B → ¬A wrote:
ioannisk wrote:"Only wrong actions would be expected to reduce the aggegate well-being of a person"

From this statement, the conditional diagram would be reduce the aggegate well-being of a person ----> Wrong actions

correct?


Ew • (∀x){[Ax • (x ≠ w)] → ~Ex}

wrong is expected to reduce the aggregate well-being of a person, and for all x, if x is an action and x is different from wrong, then x is not expected to reduce the aggregate well-being of a person

E for expected to reduce the aggregate well-being of a person
w for wrong
A for action


I have no idea if that diagram is logically correct or not, but I do know that if you diagram stuff on the LSAT like this, you are going about trying to solve the question the wrong way. It's fancy and technical looking though.

User avatar
A → B ⊨ ¬B → ¬A
Posts: 628
Joined: Tue Oct 23, 2012 5:32 pm

Re: How would you diagram this conditional statement?

Postby A → B ⊨ ¬B → ¬A » Wed Oct 23, 2013 6:30 pm

Jeffort wrote:
A → B ⊨ ¬B → ¬A wrote:
ioannisk wrote:"Only wrong actions would be expected to reduce the aggegate well-being of a person"

From this statement, the conditional diagram would be reduce the aggegate well-being of a person ----> Wrong actions

correct?


Ew • (∀x){[Ax • (x ≠ w)] → ~Ex}

wrong is expected to reduce the aggregate well-being of a person, and for all x, if x is an action and x is different from wrong, then x is not expected to reduce the aggregate well-being of a person

E for expected to reduce the aggregate well-being of a person
w for wrong
A for action


I have no idea if that diagram is logically correct or not, but I do know that if you diagram stuff on the LSAT like this, you are going about trying to solve the question the wrong way. It's cool and technical looking though.


That's how you would quantify and identify an only statement. You wouldn't really want to write this ever, but it's good to understand the relationship. It's also weird because it uses "would be expected." It's just limiting the expectation for hypothetical actions to those that are wrong, and it's saying that all other actions do not carry that expectation. The inverse of this would say every action but wrong actions is not to be expected to reduce.

User avatar
iamgeorgebush
Posts: 851
Joined: Sat Oct 05, 2013 3:57 pm

Re: How would you diagram this conditional statement?

Postby iamgeorgebush » Wed Oct 23, 2013 10:29 pm

Diagramming things the way "A → B ⊨ ¬B → ¬A" just did is not going to help you. It wouldn't help me, and I am familiar with predicate logic. You generally want to stick to simple propositional logic (and in this case, it's just simple conditional logic).

This is how I'd approach it...

Let A = it is an action
Let W = it is wrong
Let E = it is expected to reduce the aggregate well-being of a person

(E • A) --> W

(The bullet point means "and"...you could use "&" in its place, if you wanted.)

User avatar
A → B ⊨ ¬B → ¬A
Posts: 628
Joined: Tue Oct 23, 2012 5:32 pm

Re: How would you diagram this conditional statement?

Postby A → B ⊨ ¬B → ¬A » Thu Oct 24, 2013 10:51 am

iamgeorgebush wrote:Diagramming things the way "A → B ⊨ ¬B → ¬A" just did is not going to help you. It wouldn't help me, and I am familiar with predicate logic. You generally want to stick to simple propositional logic (and in this case, it's just simple conditional logic).

This is how I'd approach it...

Let A = it is an action
Let W = it is wrong
Let E = it is expected to reduce the aggregate well-being of a person

(E • A) --> W

(The bullet point means "and"...you could use "&" in its place, if you wanted.)


It should be biconditional if you do it that way. All actions are either: (1) wrong and would be expected; or (2) not wrong and would not be expected. Don't diagram any of this on the test. It will slow you down and you don't need it. Just think of how it splits actions into these two groups.

Edit: I just looked at that question and this answer choice (A) is restating the if and only if premise in the stimulus that wrong ↔ expected to reduce. Pay attention to how they say only without an if in the answer choices.

In this problem you have:
p1. expected to increase → right
p2. wrong ↔ expected to reduce
therefore, expected to be unchanged → right

If you just think of how this is grouping the actions, you have group 1 from above in the wrong ↔ reduce premise. Group 2 is everything not wrong and not reducing, which includes neutral. The conclusion says unchanged → right, and to make that jump, answer choice (C) says any action not wrong (all of group 2) is right, and this makes unchanged imply right.

User avatar
iamgeorgebush
Posts: 851
Joined: Sat Oct 05, 2013 3:57 pm

Re: How would you diagram this conditional statement?

Postby iamgeorgebush » Thu Oct 24, 2013 12:23 pm

A → B ⊨ ¬B → ¬A wrote:
iamgeorgebush wrote:Diagramming things the way "A → B ⊨ ¬B → ¬A" just did is not going to help you. It wouldn't help me, and I am familiar with predicate logic. You generally want to stick to simple propositional logic (and in this case, it's just simple conditional logic).

This is how I'd approach it...

Let A = it is an action
Let W = it is wrong
Let E = it is expected to reduce the aggregate well-being of a person

(E • A) --> W

(The bullet point means "and"...you could use "&" in its place, if you wanted.)


It should be biconditional if you do it that way. All actions are either: (1) wrong and would be expected; or (2) not wrong and would not be expected. Don't diagram any of this on the test. It will slow you down and you don't need it. Just think of how it splits actions into these two groups.

Edit: I just looked at that question and this answer choice (A) is restating the if and only if premise in the stimulus that wrong ↔ expected to reduce. Pay attention to how they say only without an if in the answer choices.

In this problem you have:
p1. expected to increase → right
p2. wrong ↔ expected to reduce
therefore, expected to be unchanged → right

If you just think of how this is grouping the actions, you have group 1 from above in the wrong ↔ reduce premise. Group 2 is everything not wrong and not reducing, which includes neutral. The conclusion says unchanged → right, and to make that jump, answer choice (C) says any action not wrong (all of group 2) is right, and this makes unchanged imply right.


No way, it should definitely NOT be a biconditional.

"Only wrong actions would be expected to reduce the aggregate well-being of a person" translates to "If an action would be expected to reduce the aggregate well-being of a person, then it must be a wrong action."

"An action would be expected to reduce the aggregate well-being of a person if and only if it is a wrong action" is NOT the same as "Only wrong actions would be expected to reduce the aggregate well-being of a person." You can't infer from the the "Only wrong actions..." proposition that a wrong action would be expected reduce the aggregate well-being of a person; you can only infer that not wrong actions would not be expected to reduce the aggregate well-being of a person (through the contrapositive). An action being wrong is the necessary condition, and the action being expected to reduce the aggregate well-being of a person is the sufficient condition.

User avatar
A → B ⊨ ¬B → ¬A
Posts: 628
Joined: Tue Oct 23, 2012 5:32 pm

Re: How would you diagram this conditional statement?

Postby A → B ⊨ ¬B → ¬A » Thu Oct 24, 2013 12:55 pm

iamgeorgebush wrote:
A → B ⊨ ¬B → ¬A wrote:
iamgeorgebush wrote:Diagramming things the way "A → B ⊨ ¬B → ¬A" just did is not going to help you. It wouldn't help me, and I am familiar with predicate logic. You generally want to stick to simple propositional logic (and in this case, it's just simple conditional logic).

This is how I'd approach it...

Let A = it is an action
Let W = it is wrong
Let E = it is expected to reduce the aggregate well-being of a person

(E • A) --> W

(The bullet point means "and"...you could use "&" in its place, if you wanted.)


It should be biconditional if you do it that way. All actions are either: (1) wrong and would be expected; or (2) not wrong and would not be expected. Don't diagram any of this on the test. It will slow you down and you don't need it. Just think of how it splits actions into these two groups.

Edit: I just looked at that question and this answer choice (A) is restating the if and only if premise in the stimulus that wrong ↔ expected to reduce. Pay attention to how they say only without an if in the answer choices.

In this problem you have:
p1. expected to increase → right
p2. wrong ↔ expected to reduce
therefore, expected to be unchanged → right

If you just think of how this is grouping the actions, you have group 1 from above in the wrong ↔ reduce premise. Group 2 is everything not wrong and not reducing, which includes neutral. The conclusion says unchanged → right, and to make that jump, answer choice (C) says any action not wrong (all of group 2) is right, and this makes unchanged imply right.


No way, it should definitely NOT be a biconditional.

"Only wrong actions would be expected to reduce the aggregate well-being of a person" translates to "If an action would be expected to reduce the aggregate well-being of a person, then it must be a wrong action."

"An action would be expected to reduce the aggregate well-being of a person if and only if it is a wrong action" is NOT the same as "Only wrong actions would be expected to reduce the aggregate well-being of a person." You can't infer from the the "Only wrong actions..." proposition that a wrong action would be expected reduce the aggregate well-being of a person; you can only infer that not wrong actions would not be expected to reduce the aggregate well-being of a person (through the contrapositive). An action being wrong is the necessary condition, and the action being expected to reduce the aggregate well-being of a person is the sufficient condition.


No. Wrong actions would be expected to reduce means if a wrong action were to occur it would be expected to reduce. Then add only.
You're half right, but Only is different from Only if.
Last edited by A → B ⊨ ¬B → ¬A on Thu Oct 24, 2013 1:24 pm, edited 1 time in total.

Pancakes12
Posts: 269
Joined: Tue Jul 02, 2013 10:13 am

Re: How would you diagram this conditional statement?

Postby Pancakes12 » Thu Oct 24, 2013 1:20 pm

I agree more with George here. But you can honestly just say:

It is expected to reduce well-being --> it is a wrong action.

User avatar
A → B ⊨ ¬B → ¬A
Posts: 628
Joined: Tue Oct 23, 2012 5:32 pm

Re: How would you diagram this conditional statement?

Postby A → B ⊨ ¬B → ¬A » Thu Oct 24, 2013 1:26 pm

Pancakes12 wrote:I agree more with George here. But you can honestly just say:

It is expected to reduce well-being --> it is a wrong action.


This is true, but wrong actions would also be expected to reduce.

Example:
Only pancakes makes a 180
is Pancakes → makes 180
makes 180 → it must be Pancakes

Only IF it's pancakes does someone make a 180
is Pancakes → makes 180 invalid
makes 180 → it must be Pancakes

Pancakes12
Posts: 269
Joined: Tue Jul 02, 2013 10:13 am

Re: How would you diagram this conditional statement?

Postby Pancakes12 » Fri Oct 25, 2013 8:49 am

A → B ⊨ ¬B → ¬A wrote:
Pancakes12 wrote:I agree more with George here. But you can honestly just say:

It is expected to reduce well-being --> it is a wrong action.


This is true, but wrong actions would also be expected to reduce.

Example:
Only pancakes makes a 180
is Pancakes → makes 180
makes 180 → it must be Pancakes

Only IF it's pancakes does someone make a 180
is Pancakes → makes 180 invalid
makes 180 → it must be Pancakes


As far as the LSAT is concerned, "only pancakes makes a 180" would be diagrammed:

Makes a 180 --> is pancakes, not the other way around

User avatar
A → B ⊨ ¬B → ¬A
Posts: 628
Joined: Tue Oct 23, 2012 5:32 pm

Re: How would you diagram this conditional statement?

Postby A → B ⊨ ¬B → ¬A » Fri Oct 25, 2013 10:12 am

Pancakes12 wrote:
A → B ⊨ ¬B → ¬A wrote:
Pancakes12 wrote:I agree more with George here. But you can honestly just say:

It is expected to reduce well-being --> it is a wrong action.


This is true, but wrong actions would also be expected to reduce.

Example:
Only pancakes makes a 180
is Pancakes → makes 180
makes 180 → it must be Pancakes

Only IF it's pancakes does someone make a 180
is Pancakes → makes 180 invalid
makes 180 → it must be Pancakes


As far as the LSAT is concerned, "only pancakes makes a 180" would be diagrammed:

Makes a 180 --> is pancakes, not the other way around


Yeah, now I feel like that lacks the certainty to be sufficient. The first one should be "made." I missed 3 lr in June so maybe I'm just retarded. I hope you make a 180 anyway.

User avatar
iamgeorgebush
Posts: 851
Joined: Sat Oct 05, 2013 3:57 pm

Re: How would you diagram this conditional statement?

Postby iamgeorgebush » Fri Oct 25, 2013 11:11 am

Dude. No. This is just wrong. I'm really not sure how to convince you otherwise, but I'll try.

Let's start with putting the proposition in different, simpler terms:

"Only mammals are dogs."

Some other ways to phrase the proposition:

"A thing is a dog only if it is a mammal."
"If it is a dog, then it is a mammal."
"All dogs are mammals."
"No dog is not a mammal."

Some ways one CANNOT phrase the proposition:

"All mammals are dogs."
"If it is a mammal, then it is a dog."
"A thing is a mammal only if it is a dog."

As you can see, from the initial statement "Only mammals are dogs," we can infer only the first logical relationship (D --> M) and its contrapositive (~M --> ~D). We CANNOT infer the reverse, M --> D! That would be flawed reverse logic! And in order to have a biconditional ("A thing is a mammal if and only if it is a dog," or "M <--> D"), we would need both "D --> M" and "M --> D."

Pancakes12
Posts: 269
Joined: Tue Jul 02, 2013 10:13 am

Re: How would you diagram this conditional statement?

Postby Pancakes12 » Fri Oct 25, 2013 11:49 am

A → B ⊨ ¬B → ¬A wrote:
Pancakes12 wrote:
A → B ⊨ ¬B → ¬A wrote:
Pancakes12 wrote:I agree more with George here. But you can honestly just say:

It is expected to reduce well-being --> it is a wrong action.


This is true, but wrong actions would also be expected to reduce.

Example:
Only pancakes makes a 180
is Pancakes → makes 180
makes 180 → it must be Pancakes

Only IF it's pancakes does someone make a 180
is Pancakes → makes 180 invalid
makes 180 → it must be Pancakes


As far as the LSAT is concerned, "only pancakes makes a 180" would be diagrammed:

Makes a 180 --> is pancakes, not the other way around


Yeah, now I feel like that lacks the certainty to be sufficient. The first one should be "made." I missed 3 lr in June so maybe I'm just retarded. I hope you make a 180 anyway.


OK, if going by the June LR score is how we're going to settle this then I win. -1 here.

Pancakes12
Posts: 269
Joined: Tue Jul 02, 2013 10:13 am

Re: How would you diagram this conditional statement?

Postby Pancakes12 » Fri Oct 25, 2013 11:52 am

I'm beginning to think he's trolling us




Return to “LSAT Prep and Discussion Forum”

Who is online

Users browsing this forum: greatspirit, Greenteachurro, mrgstephe, VMars, Yahoo [Bot] and 7 guests